2016
DOI: 10.1371/journal.pone.0163469
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unanticipated and Novel N-Acyl L-Homoserine Lactones (AHLs) Using a Sensitive Non-Targeted LC-MS/MS Method

Abstract: N-acyl L-homoserine lactones (AHLs) constitute a predominant class of quorum-sensing signaling molecules used by Gram-negative bacteria. Here, we report a sensitive and non-targeted HPLC-MS/MS method based on parallel reaction monitoring (PRM) to identify and quantitate known, unanticipated, and novel AHLs in microbial samples. Using a hybrid quadrupole-high resolution mass analyzer, this method integrates MS scans and all-ion fragmentation MS/MS scans to allow simultaneous detection of AHL parent-ion masses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 71 publications
3
72
0
Order By: Relevance
“…As previous studies reported (Morin et al, 2003;Patel et al, 2016), we observed some characteristic fragments arising from fragmentation of the lactone ring. A daughter ion with m/z 102.055 is always observed, and three others ions with m/z 56.050, 74.061, and 84.045 are usually detected.…”
Section: Hplc-hrms/ms Analysessupporting
confidence: 75%
See 1 more Smart Citation
“…As previous studies reported (Morin et al, 2003;Patel et al, 2016), we observed some characteristic fragments arising from fragmentation of the lactone ring. A daughter ion with m/z 102.055 is always observed, and three others ions with m/z 56.050, 74.061, and 84.045 are usually detected.…”
Section: Hplc-hrms/ms Analysessupporting
confidence: 75%
“…The analytical method includes full-scan MS with successive all-ion fragmentation (AIF) MS/MS scan allowing the acquisition high resolution data of the parent ion and daughter ion masses in a single chromatographic run. As described by Patel et al (2016), four characteristic fragments originating from the lactone ring in AHLs were detected in almost all of the MS/MS spectra of the AHL standards (Girard et al, 2017). One daughter ion was abundant and always present in fragmentation patterns: the 102.055 m/z ion, which corresponds to the lactone ring itself; three other ions that arose from the fragmentation of the lactone ring (the 56.050, 74.061, and 84.045 m/z fragments) were usually observed.…”
Section: Diversity Of the Emitted Acylhomoserine Lactonesmentioning
confidence: 99%
“…The confirmation of the presence of the HSL subunit was obtained by the method described by Patel et al (Patel et al, 2016). In our case, all the AHLs had all 4 diagnostic fragments at m/z 102.055, 84.045, 74.061, and 56.050 in MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, these methods are capable of generating limits of detection (LOD) in the broad nM-range (median LOD of 2.3 nM for 19 N -acyl homoserine lactone standards; range: 0.6 nM–2838.9 nM), with some compounds owing a limit of detection around 0.6 nM (for C10-HSL) (Patel et al, 2016). …”
Section: Analytical Techniquesmentioning
confidence: 99%